Effects of Extended Time Allotments on Reading Comprehension Performance of College Students With and Without Learning Disabilities. (June 2013) - Lewandowski, Lawrence; Cohen, Justin; Lovett, Benjamin J.
Students with disabilities often receive test accommodations in schools and on high-stakes tests. Students with learning disabilities (LD) represent the largest disability group in schools, and extended time the most common test accommodation requested by such students. This pairing persists despite controversy over the validity of extended time as a test accommodation. The current study examined the effects of 50% and 100% time extensions on the reading comprehension performance of college students with and without LD. Results indicated that typical students actually benefited more than the LD group when given extra time, indicating that extended time is not a test accommodation that is specific to those with a disability. Moreover, when only students with LD were given extended time, especially double time, they outperformed nondisabled peers. We discuss implications of these findings for future research as well as accommodation decisions in educational settings.